THE PERFORMANCE OF EARLY-AGE CONCRETE WITH SEAWATER CURING - M.I Retno Susilorini; Kristina Retno Dewi W; Tri Wibowo (JOURNAL OF COASTAL DEVELOPMENT, 2005)
It is well known that concrete has been implemented for marine structures. Marine environment causes physical and chemical deterioration of concrete structures, thus, there is no doubt that the durability takes an important role in concrete performance. Learning about the performance of early-age concrete is to study the maturity of concrete, which is a key of concrete durability where “Maturity Concept” attempts to predict the development of concrete properties as a function of time and temperature of curing and becomes an excellent indicator of in-place strength development and quality from fresh to hardened concrete. It is a hypothesis for this research that the compressive strength of early-age concrete cured by seawater is higher than the one cured by plain water. This research was conducted by using two methods, experimental method and analytical method. The experimental method investigated the compressive strength of concrete cylinders, with 7 days and 14 days seawater curing and plain water curing. Concrete compressive strength design, f’c, is 22.5 MPa, and varies with water-cement ratio: 0.4, 0.5, and 0.6. After 7 days and 14 days of curing, the concrete cylinders were tested by compressive testing machine. The experimental results of this research showed that the compressive strength of 7 days and 14 days concrete specimens with seawater curing is higher than those cured by plain-water, about 2.56-5.25% for 7 days old specimens and 3.39-11.87% for 14 days old specimens. The result also showed that the lower water-cement ratio, the higher concrete compressive strength would be. The analytical calculation also gave higher compressive strength to specimens cured by seawater, about 0.06-0.39% for 7 days old specimens and 0.11-0.33% for 14 days old specimens. The higher strength compressive of concrete specimens with seawater curing is provided by the existence of calcium chloride in seawater and by high temperature of seawater. The analytical result of the “Maturity Concept” has given a good performance in predicting the compressive strength of concrete very well veryfying the experimental results. The hypothesis of this research is proven, that both experimentally and analytically, the compressive strength of 7 days and 14 days old concrete specimens cured by seawater are higher than those cured by plain water.